Pendidikan Toleransi Mazhab Sunni dan Syiah di Perguruan Tinggi Islam - Huda, Ahmad Nurul; Rahim, Husni (J-PAI: Jurnal Pendidikan Agama Islam, 2023)
This research aims to studies the role model of tolerance education for Sunni and Shia schools of thought at islamic college with students who understand various theologies. This study was carried out by analyzing the policies of the leadership in supporting tolerance. And than, the researcher described the application of the educational tolerance program at islamic college in instilling a culture of tolerance for Sunni and Shia schools of thought. This study uses a qualitative research method with a phenomenological approach, which is described in a descriptive analytical manner based on experience and awareness of the phenomena that occur. The methods used in data collection are observation, interviews and documentation. The thesis statement in this study is that tolerance between Sunni and Shia at islamic college can be realized through accommodative, inclusive and humanist policies both formally in academic and non-formal programs which are supported by facilities in the form of boarding programs. The existence of empirical capital in the form of the experience of the heterogeneity of the Indonesian nation, and historical capital in the form of the contextualized romance of Sunni and Shia tolerance, can become a reference and supporting factor for the construction of tolerance education between schools of thought at islamic college.